2019
DOI: 10.1177/1534734618818301
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Skin Substitutes Versus Human Placental Membrane Products in the Management of Diabetic Foot Ulcers: A Narrative Comparative Evaluation of the Literature

Abstract: Diabetic foot ulcers (DFUs) occur in up to 25% of patients with diabetes mellitus. 1 These complex, chronic wounds are associated with increased patient morbidity 2 and decreased health-related quality of life. 3 Approximately 15% of DFUs result in lower extremity amputations, 4 and the presence of foot ulceration is an independent predictor of excess all-cause mortality among patients with diabetes. 5 Despite the global burden of DFU and its adverse sequelae, 6 outcomes following standard wound care (SWC) mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…One such promising treatment is human amnion/chorion membrane (HACM) transplantation 11,12 . These tissues are typically obtained from healthy female donors during cesarean section deliveries and then are processed in different methods, such as dehydration, cryopreservation, and decellularization 13,14 . In the middle of 20th century, HACM began to be used in the treatment of burns, venous ulcers, DFUs, and other types of chronic wounds 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…One such promising treatment is human amnion/chorion membrane (HACM) transplantation 11,12 . These tissues are typically obtained from healthy female donors during cesarean section deliveries and then are processed in different methods, such as dehydration, cryopreservation, and decellularization 13,14 . In the middle of 20th century, HACM began to be used in the treatment of burns, venous ulcers, DFUs, and other types of chronic wounds 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…14 The use of tissue-engineered allogeneic cellular wound therapies represents an emerging treatment strategy. 15 The present study highlighted the hEGF Regen-D 150 cream-based treatment was better in treating the DFUs when compared with placebo treatment. The postmarketing surveillance multicenter study of Regen-D 150 has shown significant results where we had found healthy granulation and stimulated epithelization in chronic DFUs.…”
Section: Discussionmentioning
confidence: 56%
“…Among others, Holmes et al 12 report favorable results with dynamic optical coherence tomography in the evaluation of chronic ulcers. Luck et al 13 summarize the evidence from 11 randomized controlled trials on the utility of allogeneic skin substitutes compared with human placental membrane products for diabetic foot ulcers. Elbarbary et al 14 provide evidence that add-on hyperbaric oxygen enhances healing of diabetic foot ulcers in limbs with adequate blood flow.…”
Section: Editorialmentioning
confidence: 99%